Ten Steps to Successful Breastfeeding programme to promote early initiation and exclusive breastfeeding in DR Congo: a cluster-randomised controlled trial - Dr. Marcel Yotebieng, MD; Miriam Labbok, MD; Heidi M Soeters, PhD; Jean Lambert Chalachala, MD; Bruno Lapika, PhD; Bineti S Vitta, PhD; Frieda Behets, PhD (Elsevier, 2015)
Background: Optimisation of breastfeeding practices could reduce high mortality rates in children younger than 5 years, but in DR Congo, despite near-universal breastfeeding initiation and nine of ten children still breastfeeding at 1 year of age, exclusivity remains a difficulty. We assessed the effect on breastfeeding outcomes of a short-cut implementation of a programme called the Ten Steps to Successful Breastfeeding, the key component of the Baby-Friendly Hospital Initiative (BFHI). Methods: We did a cluster-randomised controlled trial and randomly assigned health-care clinics in Kinshasa, DR Congo, to standard care (control group), BFHI steps 1-9 (steps 1-9 group), or BFHI steps 1-9 plus additional support during well-child visits (steps 1-10 group) with computer-generated random numbers used to assign matched pairs to study groups. Mothers at these clinics who had given birth to one healthy baby during enrolment, and who expressed their intentions of visiting a well-baby session at the same clinic, were eligible and received the treatment assigned to their clinic. Mother-infant pairs were excluded if the mothers intended to attend well-baby clinic visits at a different health facility, or to travel before the child was aged at least 6 months. Participants and independent interviewers were masked to group assignment (ie, they were recruited after randomisaion and training of the clinic staff and were not informed of the study scheme), but clinical staff were unmasked. BFHI steps 1-9 and 1-10 were given by health-care staff trained with the WHO/UNICEF BFHI course. The primary outcomes were breastfeeding initiation within 1 h of birth and exclusive breastfeeding at age 14 and 24 weeks, assessed at face-to-face interviews in the clinic. Analysis was by intention to treat. Prevalence ratios (PR) were adjusted for cluster effects and baseline characteristics. This trial is registered at ClinicalTrials.gov, number NCT01428232, and is closed to new participants. Findings: Between May 24, and Aug 25, 2012, we randomly assigned two eligible clinics to control, two to BFHI steps 1-9, and two to BFHI steps 1-10. We enrolled 975 eligible mother-infant pairs (304 in the control group, 363 in the steps 1-9 group, and 308 in the steps 1-10 group). 230 (76%) of infants in the control group, 263 (72%) in the steps 1-9 group, and 220 (71%) in the steps 1-10 group were breastfed within 1 h of birth; these results did not differ significantly between groups. Prevalence of exclusive breastfeeding at age 14 weeks was 89 (29%) in the control group, 237 (65%) in the steps 1-9 group (adjusted PR 2·20, 95% CI 1·73-2·77), and 129 (42%) in the steps 1-10 group (1·40, 1·13-1·74). At age 24 weeks, the prevalence of exclusive breastfeeding was 36 (12%) in the control group, 131 (36%) in the steps 1-9 group (3·50, 2·76-4·43), and 43 (14%) in the steps 1-10 group (1·31, 0·91-1·89). Interpretation: In the setting of health-care clinics in DR Congo with a high proportion of mothers initiating breastfeeding, implementation of basic training in BFHI steps 1-9 had no additional effect on initiation of breastfeeding but significantly increased exclusive breastfeeding at 6 months of age. Additional support based on the same training materials and locally available breastfeeding support materials, offered during well-child visits (ie, step 10) did not enhance this effect, and might have actually lessened it. Funding: Bill & Melinda Gates Foundation and the Carolina Global Breastfeeding Initiative at the University of North Carolina (OH, USA).